2009
DOI: 10.1111/j.1743-6109.2009.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Sexual Health: A Qualitative Research Approach on Greek Nurses’ Perceptions

Abstract: Introduction Health care professionals, especially nurses, through their contact with patients, play an important role in encouraging discussions about sexual concerns. Aim To explore perceptions on sexual health issues and how these might inhibit or enhance Greek nurses’ ability to incorporate sexual health assessment into everyday practice. Main Outcome Measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…The majority of these problems can be treated in early stages with counseling and a few numbers of them need to be treated by specialists. [30] The finding of the current study regarding sociodemographic characteristics of the studied group, the current results revealed that more than half of cervical cancer women age 40 -< 50 years, with a mean age of 42.11±10.02 years. This result was in the same line with Aktin and Ahmad (2014).…”
Section: Discussionsupporting
confidence: 47%
“…The majority of these problems can be treated in early stages with counseling and a few numbers of them need to be treated by specialists. [30] The finding of the current study regarding sociodemographic characteristics of the studied group, the current results revealed that more than half of cervical cancer women age 40 -< 50 years, with a mean age of 42.11±10.02 years. This result was in the same line with Aktin and Ahmad (2014).…”
Section: Discussionsupporting
confidence: 47%
“…Awareness-building is concerned with assisting nurses to overcome personal sexual feelings, behaviours, beliefs, attitudes, and knowledge that strongly influence the practice of nursing (Nakopoulou et al, 2009) and legitimising the importance of sexual health for nurses (Higgins, Barker, & Begley, 2006b;Krebs, 2007). From here, nurses are given Approval to engage with consumers on the topic.…”
Section: Discussionmentioning
confidence: 98%
“…There is widespread avoidance of sexual health concerns (McCann, 2010;Nakopoulou, Papaharitou, & Hatzichristou, 2009;Quinn, Happell, & Brown, 2011a), notable absence of content in nursing curricula (French, 2010;Montura et al, 2001;Shell, 2007), and absence of any reference in professional practice standards to nursing competency in Models of clinical practice have been developed to include human sexuality in nursing care (Anderson, 1990;Mick, Hughes, & Cohen, 2004;Schain, 1988;Annon, 1976;Taylor & Davis, 2006) with most progress toward addressing sexual health concerns in nursing practice occurring within the clinical speciality of Oncology. The purpose of this paper is to present and describe the development of the 5-As framework for including sexual concerns in mental health nursing practice.…”
mentioning
confidence: 98%
“…A variety of personal and contextual reasons are given as self-limiters with respect to nurses' willingness to address patients' sexuality concerns. Issues such as age and gender differences, lack of time, privacy, and knowledge and training on dealing with sexual dysfunction, and restricted perception of nursing role, discomfort, work environment-related issues, have been found by other researches (Huang, Tsai, Tseng, Li, & Lee, 2013;Kotronoulas, Papadopoulou, & Patiraki, 2009;Nakopoulou, Papaharitou, & Hatzichristou, 2009;Nicolai et al, 2013;Sung, Yeh, & Lin, 2010).…”
mentioning
confidence: 94%
“…Furthermore, Tsai et al (2013) found that nursing students' learning needs for addressing patients' sexual health care included knowledge of sexuality in health and illness, communication skills of discussing patients' intimacy, and ways to provide sexual health care. Moreso, in addition to physical issues associated with sexuality, nurses and nursing students stressed the need of further specialized training in preparing attitude to approach and selfconfidence to communication behavior (Nakopoulou et al, 2009;Sung & Lin, 2013).…”
mentioning
confidence: 99%